2022
DOI: 10.3390/healthcare10101839
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicines for Post-Acute Sequelae (Fatigue or Cognitive Dysfunction) of SARS-CoV-2 Infection: A Phase 2 Pilot Clinical Study Protocol

Abstract: Long-term sequelae refer to persistent symptoms or signs for >6 months after SARS-CoV-2 infection. The most common symptoms of sequelae are fatigue and neuropsychiatric symptoms (concentration difficulty, amnesia, cognitive dysfunction, anxiety, and depression). However, approved treatments have not been fully established. Herbal medicines are administered for 12 weeks to patients who continuously complain of fatigue or cognitive dysfunction for >4 weeks that only occurred after COVID-19 diagnoses. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Recently, herbal medicine has emerged as a potential treatment option for addressing the long‐term effects of COVID‐19, particularly fatigue and cognitive dysfunction (Jegal et al, 2022). A retrospective descriptive study highlights the frequent prescription of Hochuekkito (Bu‐Zhong‐Yi‐Qi‐Tang, TJ‐41) in Kampo medicine for managing post‐COVID fatigue (Tokumasu et al, 2022).…”
Section: Clinical Applications Of Quercetin and Quercetin‐containing ...mentioning
confidence: 99%
“…Recently, herbal medicine has emerged as a potential treatment option for addressing the long‐term effects of COVID‐19, particularly fatigue and cognitive dysfunction (Jegal et al, 2022). A retrospective descriptive study highlights the frequent prescription of Hochuekkito (Bu‐Zhong‐Yi‐Qi‐Tang, TJ‐41) in Kampo medicine for managing post‐COVID fatigue (Tokumasu et al, 2022).…”
Section: Clinical Applications Of Quercetin and Quercetin‐containing ...mentioning
confidence: 99%
“…This study was approved by the Institutional Review Board of Kyung Hee University KM Hospital (KOMCIRB 2020-12-002-001). The protocol of this study was published as a protocol paper [18] and registered at cris.nih.go.kr (KCT0006252) prior to the start of the clinical trial.…”
Section: Trial Designmentioning
confidence: 99%
“…AEs were assessed at all in-person visits occurring at 1, 5, 9, 13, 25, and 37 weeks. Detailed research methodology can be found in the previously published protocol paper [18].…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Several studies have purported that herbal medicines are effective in improving symptoms, lung function, and imaging in mild cases and in the management of COVID-19 sequelae. 25,26) Given that clinical trials have been registered and are recruiting, 27,28) it is expected that additional well-designed large-scale clinical studies will be published in the near future. 29) Despite the similarities in recruitment timeframe and symptom severity, none of the patients included in this study were admitted to a hospital due to worsening COVID-19 symptoms.…”
Section: Changes In Covid-19-relatedmentioning
confidence: 99%